A Comparative Study of the Impact of Education through the Infographic Method with the Multimedia Method in Increasing the Knowledge of Dentists and Dental Students in Birjand city Regarding the 2019 Coronavirus Disease - Azadeh Ebrahimzadeh; Zahra Mirzaie; Hamid Salehiniya; Hamid Abbaszadeh (Journal of Medical Education and Development, 2023)
Introduction: Dentists are at the forefront of viral infections such as the new coronavirus. Considering the need for dentists to increase their knowledge about emerging diseases, this study compared the impact of education through the infographic with the multimedia in informing the dentists and dental students of Birjand City about the 2019 coronavirus disease. Methods: An interventional study was done in 2022 on 196 dentists and dental students in Birjand city, who were randomly divided into groups of education through infographic (n = 98) and education through multimedia (n = 98). The educational content was the same for the groups. A 40-point test was performed before and after the educational intervention, and the results were analyzed using chi-square and independent t-tests at a significance level of P < 0.05. Results: The average pre-test scores in the infographic and multimedia groups were 28.69 ± 5.38 and 28.04 ± 6.47, respectively. There was no significant difference between the knowledge scores in the two groups before the intervention (P = 0.44). The average post-test scores in the multimedia and infographic groups were 38.83 ± 1.14 and 31.11 ± 3.19, respectively. The results of the statistical tests showed that there was a significant difference between the knowledge scores after the educational intervention (P = 0.001). Conclusion: Multimedia education is more effective than infographics in improving the level of knowledge, so the establishment of this educational method by health policymakers is recommended as an effective educational method in the field of emerging diseases.